Battery operated devices and systems : from portable electronics to industrial products - Pistoia, G. (Gianfranco) (Elsevier, 2009)
For researchers interested in devices and systems drawing power from batteries, this book will be a valuable information source. It reports on many applications in detail and presents the essentials of batteries. Links to further reading are provided through the 275 references. In chapter 1, all applications in the portable and industrial areas are introduced. Some market considerations follow with details on specific sectors. In chapter 2, basic characteristics of all primary and secondary batteries used in these applications are reviewed. The most recent trends, especially for the ubiquitous lithium ion batteries, are covered. In chapter 3, portable applications, e.g. mobile phones, notebook computers, cameras, camcorders, personal digital assistants, medical instruments, power tools, portable GPS, etc., are described with details on their electronic aspects. There is particular emphasis on the devices' power consumption and management for the implications on battery life and the devices' runtime. Battery management is also dealt with in detail, particularly as far as the charging methods are concerned. The criteria of battery choice are stressed. The comprehensive chapter on industrial applications includes aerospace, telecommunications, emergency systems, load levelling, energy storage, toll collection, different meters, data loggers, oil drilling, oceanography, meteorology, etc. The final part of this section is devoted to wireless connectivity, i.e. Wi-Fi, Bluetooth and Zigbee, which is exploited in many portable and industrial applications. Chapter 5 deals with vehicular applications. Full electric and hybrid vehicles are presented, and the role of batteries in the vehicle control systems is outlined. - A comprehensive review of battery applications. - Includes 209 figures and 62 tables - Describes state-of-the-art technological developments.